Pigs and Cattle in Gaul: The Role of Gallic Societies in the Evolution of Husbandry Practices. (17th January 2017) - Frémondeau, Delphine; Nuviala, Pauline; Duval, Colin
Abstract : In this article we present a comparative study of pig and cattle morphologies, and stable isotope analysis relating to pig demographic management at Levroux Les Arènes (Indre, France), to evaluate changes in husbandry practices between the Iron Age and the Roman period in Gallic societies. Results indicate the establishment of new production and distribution structures, probably before the second centurybc, along with the implementation of a specific size/weight selection for the specialized production of pork. Pig and cattle size evolves progressively from the end of the third centurybc . These changes are likely to be the result of an internal evolution within Gallic societies, based on local herds, but possibly they are a response to a broader changing economic climate. Within the Western Roman Empire, each province, and Italy, follows its own evolutionary pattern, which also differs between pig and cattle, suggesting that each region adapted its husbandry strategies according to its agro-pastoral characteristics, capacities, or ambitions. Abstract : Pour mieux comprendre les changements dans les pratiques d'élevage survenus entre l'âge du Fer et la période romaine en Gaule, cet article présente l'étude combinée de l'évolution morphologique des porcs et des bœufs et de la gestion démographique des porcs du site de Levroux Les Arènes (Indre, France). Les résultats indiquent la mise en place, sans doute avant le deuxième siècle av. J.-C., de nouveaux systèmes de production et de distribution, et l'existence d'une sélection des porcs abattus à Levroux Les Arènes en fonction d'un format - ou d'un poids – pour une production spécialisée de viande. En Gaule, la taille des porcs et des bœufs évolue progressivement à partir de la fin du troisième siècle av. J.-C. Ces changements résultent vraisemblablement d'une évolution interne aux sociétés gauloises, basée sur des cheptels locaux, mais potentiellement en réponse à des changements économiques plus globaux. Au sein de l'Empire Romain d'Occident, chaque province, ainsi que l'Italie elle-même, semble suivre son propre schéma évolutif, qui en outre diffère entre porcs et bovins, ce qui suggère que chaque région a pu adapter ses stratégies d'élevage en accord avec ses propres caractéristiques agro-pastorales, ses capacités ou ses ambitions. Abstract : In diesem Artikel wird eine vergleichende Untersuchung der Morphologie von Schweinen und Rinder vorgelegt sowie eine Analyse stabiler Isotopen, die die Führung des Schweinebestands in Levroux Les Arènes (Indre, Frankreich) betrifft, um die Veränderungen in den Tierhaltungspraktiken zwischen der Eisenzeit und der Römerzeit in der gallischen Gesellschaft auszuwerten. Unsere Ergebnisse zeigen, dass neue Produktionsstrukturen und Vertriebssysteme wahrscheinlich vor dem 2. Jahrhundert v. Chr. eingeführt wurden, und dass bestimmte Größen/Gewichte in der spezialisierten Erzeugung von Schweinefleisch ausgesucht wurden. Die Statur der Schweine und Rinder nimmt zunehmend vom späten 3. Jahrhundert an. Diese Veränderungen sind wahrscheinlich auf eine Entwicklung innerhalb der gallischen Gesellschaft zurückzuführen, die sich auf einheimische Herden stützte. Vielleicht waren sie aber auch eine Reaktion zu Umwandlungen im weiteren wirtschaftlichen Umfeld. Im westlichen Römerreich folgt jede Provinz, und auch Italien, ihren eigenen Entwicklungsprozess, der sich für Schweine und Rinder unterschiedlich entfaltet; dies deutet darauf hin, dass jedes Gebiet seine Tierhaltungsstrategie je nach seinen agropastoralen Eigenschaften, Leistungsfähigkeiten und Ziele angepasst hatte. Translation by Madeleine Hummler